Answer:
From the question it is given that x<0 and y>0 or in other words x is negative and y is positive.
(a)x y : x is negative and y is positive
⇒negative x positive = negative
Therefore, xy is negative
(b)x[tex]y^{2}[/tex] : x is negative and [tex]y^{2}[/tex] is positive
⇒negative x positive = negative
Therefore, x[tex]y^{2}[/tex] is negative
(c) (x − y)xy : x is negative and [tex]y^{2}[/tex] is positive
⇒(x − y) is negative and xy is negative {from (a)}
⇒negative x negative = positive
Therefore, (x-y)xy is negative
(d) y(y − x): x is negative and y is positive
here y - x is positive
⇒positive x positive = positive
Therefore, (y-x)y is negative